2023
DOI: 10.1021/acs.est.3c01980
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality Determines the Variations of Biofilm Microbiome and Antibiotic Resistome in a Pilot-Scale Chlorinated Drinking Water Distribution System Deciphered by Metagenome Assembly

Abstract: Understanding the biofilm microbiome and antibiotic resistome evolution in drinking water distribution systems (DWDSs) is crucial to ensure the safety of drinking water. We explored the 10 month evolution of the microbial community, antibiotic resistance genes (ARGs), mobile gene elements (MGEs) co-existing with ARGs and pathogenic ARG hosts, and the ARG driving factors in DWDS biofilms using metagenomics assembly. Sampling season was critical in determining the microbial community and antibiotic resistome shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Bacterial community composition is usually regarded as the most important factor in driving shifts of ARG composition in plant–soil continuums. However, we found that fungi can also influence the composition of ARGs in the xylem (Figure S11). Fungi can indirectly influence antibiotic resistome by affecting ARG bacterial hosts, such as providing nutrients to feed bacteria, secreting antibiotics to antagonize bacteria, or competing for resources with bacteria. , For example, Talaromyces and Penicillium , belonging to Ascomycota, can produce a variety of secondary metabolites with antibacterial activities, thus likely playing a role in shaping the antibiotic resistome. , …”
Section: Discussionmentioning
confidence: 86%
“…Bacterial community composition is usually regarded as the most important factor in driving shifts of ARG composition in plant–soil continuums. However, we found that fungi can also influence the composition of ARGs in the xylem (Figure S11). Fungi can indirectly influence antibiotic resistome by affecting ARG bacterial hosts, such as providing nutrients to feed bacteria, secreting antibiotics to antagonize bacteria, or competing for resources with bacteria. , For example, Talaromyces and Penicillium , belonging to Ascomycota, can produce a variety of secondary metabolites with antibacterial activities, thus likely playing a role in shaping the antibiotic resistome. , …”
Section: Discussionmentioning
confidence: 86%